PERAN KEUANGAN MIKRO SYARIAH PADA PERKEMBANGAN INDUSTRI HALAL DI DEVELOPING EIGHT (D-8) ISLAMIC COUNTRIES: BUKTI DARI TREN PENELITIAN 2018-2023 - Jauhari, Fiki Afif; Karim Amirullah, Malik Abd.; Azizah, Siti Nur; Hassan, Shahir Akram (Ekonomi Islam, 2024)
The spectrum of the halal ecosystem can be developed through collaboration between Islamic microfinance and the halal industry. This idea needs to be substantiated through published scientific research to trace its role and development. This study aims to examine the role of Islamic microfinance in the development of the halal industry in D-8 Islamic countries through published international research. The research employs bibliometric analysis using the VOSviewer application. The data for this study consists of 100 articles from 2018 to 2023, collected from international journal platforms most frequently used by scholars. The findings of this study reveal that research trends on the role of Islamic microfinance primarily focus on poverty alleviation, economic empowerment, and economic sustainability in D-8 countries. However, there is no specific discussion on the role of Islamic microfinance in the halal industry. Additionally, the study identifies obstacles faced by Islamic microfinance institutions in supporting the development of the halal industry, including (1) production, authentication, and certification; (2) ownership and control; (3) training and capacity building; and (4) anti-halal groups and economic Islamophobia. The implications of this research can serve as a reference for identifying future research gaps. Keywords: Islamic microfinance, Halal industry, Poverty alleviation.